Aldoxime Metabolism Is Linked to Phenylpropanoid Production in Camelina sativa - Zhang, Dingpeng; Song, Yeong Hun; Dai, Ru; Lee, Tong Geon; Kim, Jeongim (Frontiers in Plant Science, 2020)
Plants produce diverse secondary metabolites. Although each metabolite is made through its respective biosynthetic pathway, plants coordinate multiple biosynthetic pathways simultaneously. One example is an interaction between glucosinolate and phenylpropanoid pathways in Arabidopsis thaliana. Glucosinolates are defense compounds made primarily from methionine and tryptophan, while phenylpropanoids are made from phenylalanine. Recent studies have shown that the accumulation of glucosinolate intermediate such as indole-3-acetaldoxime (IAOx) or its derivatives represses phenylpropanoid production via the degradation of phenylalanine ammonia lyase (PAL) functioning at the entry point of the phenylpropanoid pathway. Given that IAOx is a precursor of other bioactive compounds other than glucosinolates and that the phenylpropanoid pathway is present in most plants, we hypothesized that this interaction is relevant to other species. Camelina sativa is an oil crop and produces camalexin from IAOx. We enhanced IAOx production in camelina by overexpressing Arabidopsis CYP79B2 which encodes an IAOx-producing enzyme. The overexpression of AtCYP79B2 results in increased auxin content and its associated morphological phenotypes in camelina but indole glucosinolates were not detected in camelina wild type as well as the overexpression lines. However, phenylpropanoid contents were reduced in AtCYP79B2 overexpression lines suggesting a link between aldoxime metabolism and phenylpropanoid production. Interestingly, the expression of PALs was not affected in the overexpression lines although PAL activity was reduced. To test if PAL degradation is involved in the crosstalk, we identified F-box genes functioning in PAL degradation through a phylogenetic study. A total of 459 transcript models encoding kelch-motifs were identified from Camelina sativa database. Among them, the expression of CsKFBs involving in PAL degradation is up-regulated in the transgenic lines. Our results suggest a link between aldoxime metabolism and phenylpropanoid production in camelina and a molecular mechanism behind the crosstalk is conserved in Arabidopsis and camelina.